Classificação das hipersuperfícies lorentzianas de R1n para Rn1+1 - Escobar Montecino, Claudia Evelyn (2015)
In this dissertation we present a result of classi cation of isometric hypersurfaces between Lorentz-Minkowski spaces due to L. K. Graves [5], which generalizes a classic theorem of Hartman and Nirenberg [7], where hypersurfaces were classi ed among Euclidean spaces. The technique we use in this classi cation of hypersurfaces is to rst study the completeness of the relative nullity foliation, and split the demonstration in two cases depending of the foliation be degenerate or not degenerate.